Influence of Human Resource Management on Academic Performance of Trainees in Public Primary Teacher Training Colleges in Kenya - Edabu, Paul; Wagithunu, Margaret Nyambura; Sinan, Ganatusanga Haroon (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2018)
Importance of human resource management on academic performance of teacher-trainees in teacher training colleges cannot be over-emphasized. However, academic performance of teacher-trainees has been dismal and continues to be on a downward trend. The purpose of this study was to investigate the influence of human resource management on academic performance of trainees in public primary teacher training colleges in Kenya. The study was guided by the human capital theory. The study adopted mixed methods approach and thus applied concurrent triangulation research design. Qualitative data were analyzed thematically along the objectives and presented in narrative forms, whereas quantitative data was analyzed descriptively and inferentially using Chi-Square test. The study established that human resource management does effectively influence teacher trainees’ academic performance in public TTCs in Kenya. The study concludes that though the human resources are important, but were in adequate to influence on trainees’ academic performance in public PTTCs in Kenya. Improvement on human resource management shall greatly improve trainees’ academic performance in PTTCs in Kenya. The study recommends that PTTCs should have enough, adequate human resources.